Ambient Air Quality and General Health Outcomes in Nigde (Turkey) between 2011 and 2017 - Ertan Kara; Hasan Göksel Özdilek; Emine Erman Kara; Fatih Balcı; Burcu Mestav (Tehran University of Medical Sciences, 2021)
Background: We aimed to provide information for health practitioners and other related people about the association between ambient air quality and adverse health outcomes in the general population of Nigde, a central Turkish city, within the context of current health data epidemiological evidence. Methods: The present study highlights the connection between health problems and time series of particulate matter (PM10) and sulphur dioxide (SO2) in Nigde, Turkey between 2011 and 2017. Significant morbidity is linked to ambient air pollution, resulting in a significant economic cost to society. Results: We found that the required funds to treat cancers and chronic obstructive pulmonary disease triggered by ambient air pollution in Nigde, exceed 9 million US dollars per year, even when only the city center is taken into account. Conclusion: As Turkish cities grow and urban population density increases, air pollution issues need to be given priority in order to protect the health of the public and support sustainable development for future generations. It is recommended that particulate matter concentration in this urban center should be significantly reduced to minimize health problems.